Mathematical analysis of the Navier-Stokes equations : Cetraro, Italy 2017 /: Cetraro, Italy 2017. (2020) - Hieber, Matthias, 1959-; Robinson, James C (James Cooper), 1969-; Shibata, Yoshihiro
No abstract available